Creative Learning Through the Use of Simulation to Teach Nursing Students Screening, Brief Intervention, and Referral to Treatment for Alcohol and Other Drug Use in a Culturally Competent Manner. (July 2018) - Fioravanti, Marie A.; Hagle, Holly; Puskar, Kathy; Knapp, Emily; Kane, Irene; Lindsay, Dawn; Terhorst, Lauren; Mitchell, Ann M.
Introduction: Cultural competency is an integral component in undergraduate nursing education to provide patient-centered care and addressing patients' cultural differences. Students need to consider the prevalence of alcohol and other drug use/misuse in patients from all cultures. This project combines cultural competency education, simulation, and educating students to use screening, brief intervention, and referral to treatment for alcohol and other drug use.Method: Culturally diverse simulation scenarios were developed and used in the simulation lab with students to reduce stigma surrounding other cultures while learning an evidence-based practice to screen and intervene with patients who use/misuse substances.Results: Results show students value simulation and 91% of the students felt that they were able to apply culturally competent knowledge after the simulation experience.Discussion: Cultural competency principles can be embedded in teaching the broader evidence-based practice of screening, brief intervention, and referral to treatment with undergraduate students. This is a replicable teaching methodology that could be adapted in other schools of nursing.